Discursive constructions of social and environmental accounting in Brazil: the case of Petrobras. - Voss, Barbara de Lima (2016)
In the 29 years following \"Our Common Future\" by the United Nations, there is considerable debate among governments, civil society, interest groups and business organisations about what constitutes sustainable development, which constitutes evidence for a contested discourse concerning sustainability. The purpose of this study is to understand this debate in the developing economic context of Brazil, and in particular, to understand and critique the social and environmental accounting [SEA] discursive constructions relating to the State-owned, Petrobras as well as to understand the Brazilian literature on SEA. The discourse theory [DT]-based analysis employs rhetorical redescription to analyse twenty-two reports from Petrobras from 2004-2013. I investigate the political notions by employing the methodological framework of the Logics of Critical Explanation [LCE]. LCE engenders five methodological steps: problematisation, retroduction, logics (social, political and fantasmatic), articulation and critique. The empirical discussion suggests that the hegemony of economic development operates to obfuscate, rhetorically, the development of sustainability, so as to maintain the core business of Petrobras conceived as capital accumulation. Equally, these articulations also illustrate how the constructions of SEA operate to serve the company\'s purpose with few (none) profound changes in integration of sustainability. The Brazilian literature on SEA sustains the status quo of neo-liberal market policies that operate to protect the dominant business case approach to maintain an agenda of wealth-creation in relation to social and environmental needs. The articulations of the case manifested in policies regarding, for example, corruption, which involved over-payments for contracts and unsustainable practices relating to the use of fossil fuels and demonstrated that there was antagonism between action and disclosure. The corruption scandal that emerged after SEA disclosures highlighted the rhetorical nature of disclosure when financial resources were subtracted from the company for political parties and engineering contractors hid facts through incomplete disclosures. The articulations of SEA misrepresent a broader context of the meanings associated with sustainability, which restricted the constructions of SEA to principally serve and represent the intention of the most powerful groups. The significance of SEA, then is narrowed to represent particular interests. The study argues for more critical studies as limited Brazilian literature concerning SEA kept a \'safe distance\' from substantively critiquing the constructions of SEA and its articulations in the Brazilian context. The literature review and the Petrobras\' case illustrate a variety of naming, instituting and articulatory practices that endeavour to maintain the current hegemony of development in an emerging economy, which allows Petrobras to continue to exercise significant profit at the expense of the social and environmental. The constructed idea of development in Petrobras\' discourses emphasises a rhetoric of wider development, but, in reality, these discourses were the antithesis of political, social and ethical developmental issues. These constructions aim to hide struggles between social inequalities and exploitation of natural resources and constitute excuses about a fanciful notion of rhetorical and hegemonic neo-liberal development. In summary, this thesis contributes to the prior literature in five ways: (i) the addition of DT to the analysis of SEA enhances the discussion of political elements such as hegemony, antagonism, logic of equivalence/difference, ideology and articulation; (ii) the analysis of an emerging economy such as Brazil incorporates a new perspective of the discussion of the discourses of SEA and development; (iii) this thesis includes a focus on rhetoric to discuss the maintenance of the status quo; (iv) the holistic structure of the LCE approach enlarges the understanding of the social, political and fantasmatic logics of SEA studies and; (v) this thesis combines an analysis of the literature and the case of Petrobras to characterise and critique the state of the Brazilian academy and its impacts and reflections on the significance of SEA. This thesis, therefore, argues for more critical studies in the Brazilian academy due to the persistence of idea of SEA and development that takes-for-granted deep exclusions and contradictions and provide little space for critiques.